2014
DOI: 10.1503/cjs.029213
|View full text |Cite
|
Sign up to set email alerts
|

Massive panniculectomy: a novel method of treatment of postlaparotomy wound dehiscence in morbid obesity

Abstract: E53

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Compared to our study, Zhamak et al did not compare the difference in body mass index (BMI) between the two groups, but obese patients were more prone to abdominal wound dehiscence. 17 , 42 , 43 Moreover, some studies reported that retention suture techniques do not prevent the occurrence of postoperative abdominal wound dehiscence. 3 , 11 , 44 Poole et al 11 noted that retention sutures were not essential if the fascia was properly closed.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to our study, Zhamak et al did not compare the difference in body mass index (BMI) between the two groups, but obese patients were more prone to abdominal wound dehiscence. 17 , 42 , 43 Moreover, some studies reported that retention suture techniques do not prevent the occurrence of postoperative abdominal wound dehiscence. 3 , 11 , 44 Poole et al 11 noted that retention sutures were not essential if the fascia was properly closed.…”
Section: Discussionmentioning
confidence: 99%